Upaya Meningkatkan Hasil Belajar Fisika Melalui Model Pembelajaran Terpadu Tipe Connected Pada Siswa Kelas Xii Mipa 3 Sma Negeri 3 Bone - St Hawang (Universitas Negeri Makassar, 2018)
This research aims to improve student physics learning result of class XII MIPA 3 SMA Negeri 3 Bone through Connected type integrated learning model. The subjects of this study are the students of class XII MIPA 3 SMA Negeri 3 Bone Lesson Year 2014/2015 odd semester as many as 30 students consisting of 14 male students and 16 female students. This research is conducted in 2 cycles, each cycle consists of components, namely: action planning, action implementation, observation and reflection. The data collection techniques used are the final test of Cycle I, the final test of Cycle II and the observation sheet. The result of quantitative and qualitative descriptive analysis is the result of physics study of class XII MIPA 3 SMA Negeri 3 Bone on Cycle I average score obtained 67 or (67%) and standard deviation 9.72 from ideal score 100, subject